AUTOCAD FOR INTERIOR DESIGN AND SPACE PLANNING - KIRKPATRICK, JAMES. KIRKPATRICK, BEVERLY, BFA, NCIDQ, ADJUNCT FACULTY. ASSADIPOUR, HOSSEIN (PEACHPIT PRESS, 2021)
teaches the commands and features of AutoCAD 2022 and demonstrates how to make the most of these powerful tools to complete any interior design or space planning project. Covering both two- and three-dimensional drawings, it provides abundant exercises that walk learners step-by-step through the use of AutoCAD prompts and commands. Using numerous, up-to-date illustrations, the authors dont just capture the essence of this powerful program; they help students thoroughly understand its role in professional interior design, architecture, and space planning. This fully-updated guide: AutoCAD 2022 for Interior Design and Space Planning Covers the new AutoCAD 2022 interface Progresses from basic commands to complex drawing exercises Provides over 100 exercises and projects Introduces several new projects appropriate for interior design, space planning, and architecture students.